Pengembangan Instrumen Penilaian Keterampilan Menyimak (Mahārah al-Istima’) dalam Pembelajaran Bahasa Arab - M. Riza Pahlefi (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2022)
Listening skill is one the most important skills. Without adequate listening skills, a person will find it difficult to communicate. Listening skills in Arabic need to improved through structured and systematic efforts. To measure the ability of listening skills, a measuring instrument is needed in the form of an assessment instrument, in this case a listening skill test. The aim is to determine the level of students’ skills in listening to Arabic. This paper tries to explain more specifically the development of an assessment instrument for listening skills (mahārah al-istima'), the types of tests, and the process and examples of developing an assessment instrument in learning Arabic.